The Influence of Damping on Vibration Induced by High-Speed Trains - Dimitrovová, Zuzana (2010)
Passage of high-speed trains may induce high ground and track vibrations, which, besides increasing wheel, rail and track deterioration, may have a negative impact on the vehicle stability and on the passengers comfort. In this paper two distinct analyses are presented. The first one is dedicated to efficient decoupling of rail and soil vibrations by suggesting new interface materials in rail-sleeper fixing system, i.e. in the part where damping efficiency can be directly controlled and tested. The second analysis concerns with an adequate model of soils damping. Proper understanding and correct numerical simulation of this behaviour can help in suggesting soil improvement techniques.